Theaters in 19th Century cities and path dependence on contemporary cultural policies (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article presents a reflection on the reasons why cities that had theater in the past show a greater degree of institutionality of their cultural policies in relation to other cities. Therefore, through a case study of the state of Rio Grande do Sul, a survey of historical data was carried out on the presence of theater in cities and on the institutionality of cultural policies. The analysis of the results was based on two theoretical-methodological approaches: the concept of path dependence and the concept of civic community. Thus, the existence of certain central institutions for current cultural policies was confronted with the existence of theatrical buildings in the 19th century. It was found that the cities that in the 19th century had theatrical movements to the point of enabling the construction of these buildings, left a political and social legacy. On average, these cities have cultural policies with a higher degree of institutionality than the others.
Keywords: Theater building; Cultural policy; th dependence; Civic community